1995
DOI: 10.1093/oxfordjournals.jae.a036821
|View full text |Cite
|
Sign up to set email alerts
|

The Macroeconomic Impact of AIDS in Malawi: a Dualistic, Labour Surplus Economy

Abstract: This paper simulates the macroeconomic effects of the AIDS epidemic in Malawi. This is done by using Bulatao's (1990) predictions of the disease's demographic impact in a dual-economy macro model. The with-AIDS scenario is compared with a counterfactual no-AIDS scenario to assess the impact of the disease if it spreads unchecked. The results suggest that by the year 2010, Malawian real GDP could be as much as 10% smaller than it would have been in the absence of the AIDS epidemic. The impact on per capita … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 2 publications
2
30
0
1
Order By: Relevance
“…used a Solow type growth model to study the growth effects of AIDS in Malawi. This model was extended in Cuddington and Hancock (1995) to allow a dualistic labor surplus economy and in to include demographic and epidemic equations that can be used to study how AIDS related policies impact the macroeconomy. Similar conclusions concerning sizeable aggregate effects have been reported by Arndt and Lewis (2000).…”
Section: Introductionmentioning
confidence: 99%
“…used a Solow type growth model to study the growth effects of AIDS in Malawi. This model was extended in Cuddington and Hancock (1995) to allow a dualistic labor surplus economy and in to include demographic and epidemic equations that can be used to study how AIDS related policies impact the macroeconomy. Similar conclusions concerning sizeable aggregate effects have been reported by Arndt and Lewis (2000).…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that, in the absence of effective treatment, substantial productivity losses – on the order of a one percent reduction in gross domestic product (GDP) growth per year – could occur in countries with generalized HIV epidemics [6], [49], [62], [63], [64], [65], [66].…”
Section: Discussionmentioning
confidence: 99%
“…Cuddington and Hancock used a neoclassical one sector, two factor growth models to predict economic growth in Tanzania and Malawi [12]. They found that over the period 1985-2010, average annual GDP growth would be reduced by 1.1% points in Tanzania and 1.5 percentage points in Malawi.…”
Section: Sharp Investigated the Economic Impact Of Hiv/aids In Russia;mentioning
confidence: 99%